СТАН ВІТРОВОЇ ЕНЕРГІЇ В ПОЛЬЩІ - Dolega, W. (Інститут електродинаміки НАН України, Київ, 2018)
The process of current and future wind power development in Poland is analysed. Wind power worldwide and wind power in Poland are shown. Technical, economical and market potential of wind energy in Poland is defined. Analysis and assessment of wind power market in Poland in technical, economical and environmental aspects is made. Perspectives of wind power development up to 2020 are described. References 10, tables 2.